Answer: g(x) = -(1/2)*x + 3.
Explanation:
First, let's define a reflection over the x-axis.
If we have a point (x, y) and we reflect it over the x-axis, our new point will be (x, -y).
Now, when we have a function
f(x) = y, the points can be written as:
(x, y = f(x) ) = (x, f(x))
Then, after the reflection over the x-axis, we have:
(x, y = g(x)) = (x, -f(x))
So now we have g(x) = -f(x)
and we know that f(x) = (1/2)*x - 3
then our new function is g(x) = y = -f(x) = -( (1/2)*x - 3) = -(1/2)*x + 3.
g(x) = -(1/2)*x + 3.